Researches of deportations in Estonia: contemporary situation and perspectives. - Rahi-Tamm , Aigi (Genocidas ir rezistencija, 2025)
The word ‘deportations’ reminds most Estonians of two major mass operations: the June 1941 deportation and the March 1949 deportation. These operations were carried out simultaneously in all three Baltic states. The fact that there were smaller-scale deportations in addition to these two is largely unknown. It is also not known that 1948 was the year of the deportation of many Lithuanian citizens, and that in May of that year a major deportation operation was carried out in Lithuania. Although much has been written about the deportations in recent decades, the general level of knowledge about these events is still relatively low. What have we done in the last twenty years in the field of research into Estonian deportations? First, the names of the exiles have been published. The most active in this field was the association of exiles Memento. They were based on personal files. They contain the following typical data: name of the exile, date of birth, place of residence at the time of deportation, date of adoption of the deportation order, place and date of deportation, date of release from deportation or death, etc.
Keywords: Estonia; deportations; Soviet occupation